PENGEMBANGAN MEDIA VIDEO BIOTEISTIK BERBASIS AL-QUR’AN UNTUK MENINGKATKAN SPIRITUAL SISWA - Majdi, Muhamad (Penerbit Widina, Widina Media Utama, 2025)
This research aims to develop biotheistic-based learning media that integrates verses from the Koran in class XII Biology material at MANU Putera Buntet Islamic Boarding School in Cirebon in order to increase students' spiritual dimensions. The method used is Research Development (RD) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) design model. The research results show that the learning media developed is suitable for implementation after being evaluated by several experts based on validation from material and media experts. Apart from that, the spiritual attitude questionnaire filled out by students showed an increase in their spiritual dimension after using this learning media. The largest percentage showing positive changes was recorded in the aspects of being grateful for God's blessings and respecting other people's worship, which each reached 96.7%. Biotheistic-based learning media has been proven to improve students' spiritual attitudes. Indications include increasing understanding of Islamic concepts through Al-Qur'an-based videos, frequency of worship such as prayer and reading the Al-Qur'an, as well as positive attitudes towards the values of honesty, responsibility and empathy.ABSTRAKPenelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis bioteistik yang mengintegrasikan ayat-ayat Al-Qur’an pada materi Biologi kelas XII di MANU Putera Buntet Pesantren Cirebon guna meningkatkan dimensi spiritual siswa. Metode yang digunakan adalah Research Development (RD) dengan model desain ADDIE (Analysis, Design, Development, Implementation, Evaluation). Hasil penelitian menunjukkan bahwa media pembelajaran yang dikembangkan layak diimplementasikan setelah dievaluasi oleh beberapa ahli berdasarkan validasi ahli materi dan media. Selain itu, angket sikap spiritual yang diisi oleh siswa menunjukkan peningkatan dalam dimensi spiritual mereka setelah menggunakan media pembelajaran ini. Persentase terbesar yang menunjukkan perubahan positif tercatat pada aspek bersyukur atas nikmat Tuhan dan menghormati ibadah orang lain, yang masing-masing mencapai 96.7%. Media pembelajaran berbasis bioteistik terbukti meningkatkan sikap spiritual siswa. Indikasinya meliputi peningkatan pemahaman konsep keislaman melalui video berbasis Al-Qur’an, frekuensi ibadah seperti shalat dan membaca Al-Qur’an, serta sikap positif terhadap nilai kejujuran, tanggung jawab, dan empati.